Exploring Sleep Quality as a Modifiable Risk Factor for Suicidal Ideation among Young Students: Sleep Quality as a Modifiable Risk Factor for Suicidal Ideation - Imran, Manahl; Farooq, Irzah; Ahmad, Nadeem (Pakistan BioMedical Journal, 2025)
Sleep quality is a key modifiable factor that can influence suicidal ideation. While poor sleep is linked to suicidal thoughts, there is limited research on its effects in non-clinical young Students. Objectives: To examine how sleep disturbances, influenced by environmental factors such as living conditions and lifestyle, are related to suicidal ideation among students. Methods: A cross-sectional survey was conducted at the University of Punjab, Lahore, Pakistan, from March to June 2025. A total of 150 Young Students aged 15-30 years were recruited through purposive sampling. Participants completed the 13-item Sleep–Suicide Ideation Rating Scale (S-SIRS), a self-developed questionnaire designed to assess sleep quality and its perceived impact on suicidal thoughts. The S-SIRS was validated through reliability testing (Cronbach’s α = 0.748) and expert evaluation for content validity. Data analysis included Spearman’s correlation to explore the relationship between sleep disturbances and suicidal ideation, non-parametric tests for group comparisons, and Firth’s penalized-likelihood logistic regression to identify key predictors and address class imbalance. Results: A significant positive correlation was found between sleep disturbances and suicidal ideation (ρ=0.402, p<0.001). Hostel residents and female reported higher levels of both sleep disturbances and suicidal ideation. Sleep impairment was the strongest predictor, with each unit increase in sleep disturbance raising the odds of suicidal ideation by 23.3% (OR = 1.233, p<0.001). Conclusions: Sleep disturbances are strongly linked to suicidal ideation among students, with environmental factors influencing this relationship.